2009
DOI: 10.1007/bf03180579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of letrozole on bone biomarkers and femur fracture in female rats

Abstract: We aimed to investigate the effects of the aromatase inhibitor letrozole on femur fracture and serum levels of alkaline phosphatase (ALP), calcium and phosphate in female rats. Intact 32 Sprague-Dawley female rats were divided into four groups (n=8): control, letrozole 0.2 , letrozole 1 (treatment of 0.2 and 1 mg/kg for six weeks) and recovery (letrozole-treated 1 mg/kg for six weeks then allowed to recover for two weeks). Besides, 24 ovariectomized rats were divided into three groups (n=8): ovariectomized+con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Letrozole pretreatment for 1 month in ovotoxic mice resulted in further reduction in ALP and HxP and enhanced TRAP activity in both femoral epiphysis and lumbar vertebrae indicating significantly enhanced bone turnover. This is in agreement with clinical and preclinical studies showing bone loss with letrozole. While ALP is a bone formation marker and represent osteoblastic activity , both TRAP and HxP are considered markers of bone resorption .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Letrozole pretreatment for 1 month in ovotoxic mice resulted in further reduction in ALP and HxP and enhanced TRAP activity in both femoral epiphysis and lumbar vertebrae indicating significantly enhanced bone turnover. This is in agreement with clinical and preclinical studies showing bone loss with letrozole. While ALP is a bone formation marker and represent osteoblastic activity , both TRAP and HxP are considered markers of bone resorption .…”
Section: Discussionsupporting
confidence: 92%
“…Because exemestane also reduced ALP in the femoral epiphysis, it is discernible that it may impair bone formation in femoral epiphysis while having no effect on bone resorption. Thus, there seems to be a differential profile of the two aromatase inhibitors on bone biomarkers which is also in agreement with some previous reports [6,45]. However, our results differ from the study by McCloskey and co-workers (2007) which reported all three aromatase inhibitors viz.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, microCT-scanning results indicated that following 4 and 6 weeks post-surgery, the fracture repair indices, including BV/TV, BS/BV, TB.TH, TB.N and TB.SP, were significantly improved in the PDLLA group compared with the control group. ALK and OPG were expressed in the bone tissue, specifically in osteoblastic lineages and their serum concentrations were considered as the markers for the evaluation of osteogenesis during development and bone formation throughout fracture healing (23,24). The results of the current study indicate that at weeks 4 and 6 following intramedullary fixations for osteotomy, the serum levels of ALK and OPG were significantly increased in the PDLLA group, compared with the control.…”
Section: Discussionmentioning
confidence: 58%
“…Kumru et al ( 12 ) suggested that neither anastrozole nor letrozole had clear effects on bone mass density (both vertebral and femoral) of intact female rats. On the other hand, Yonden et al ( 13 ) observed that letrozole increased the risk of femoral fracture and of bone biomarkers, including alkaline phosphatase and phosphate.…”
Section: Introductionmentioning
confidence: 99%